2016
DOI: 10.1007/s12026-016-8870-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of adenosinergic pathway in human autoimmune diseases

Abstract: Autoimmune diseases are characterized by the abnormal immune response against self-tissue, which are caused by the failure of nature immune homeostasis. Nature immune homeostasis represents the normal state of appropriate immune response to nonself-antigen and unresponsiveness to self-antigens. In normal situation, immune homeostasis is regulated by immunosuppressive signal and immunostimulating signal together. Accumulating data have demonstrated that the adenosinergic pathway played key roles in immune suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
2
26
0
4
Order By: Relevance
“…Thus, down-regulation of CD73 on B cells might tip the balance toward higher AMP concentrations and lower ADO concentrations. It is important to note that different studies have shown that a disturbance in the adenosinergic pathway can lead to an imbalance of pro-and anti-inflammatory effects depending on the local environment and ADO concentration [58,[60][61][62]; therefore, our data add to the hypothesis that lower concentrations of ADO might be detrimental by causing the increased chronic immune activation observed during chronic HIV infection [2,63].…”
Section: Discussionsupporting
confidence: 52%
“…Thus, down-regulation of CD73 on B cells might tip the balance toward higher AMP concentrations and lower ADO concentrations. It is important to note that different studies have shown that a disturbance in the adenosinergic pathway can lead to an imbalance of pro-and anti-inflammatory effects depending on the local environment and ADO concentration [58,[60][61][62]; therefore, our data add to the hypothesis that lower concentrations of ADO might be detrimental by causing the increased chronic immune activation observed during chronic HIV infection [2,63].…”
Section: Discussionsupporting
confidence: 52%
“…Deletion of CD39 and CD73 leads to higher levels of anti-RNP antibodies in response to pristane, with CD73 deletion in particular promoting expansion of splenic B cell and T cell populations that likely contribute to autoantibody production. Within the T cell compartment, it is notable that some of these changes (expansion of effector/memory T cells and T H 17 cells) were present independent of pristane administration, which would fit with a general predisposition toward inflammation and autoimmunity conferred by loss of ectonucleotidase activity ( 11 , 39 , 40 ). For example, protective roles for ectonucleotidases have been suggested in rheumatoid arthritis ( 41 , 42 ), juvenile idiopathic arthritis ( 43 ), inflammatory bowel disease ( 44 , 45 ), autoimmune hepatitis ( 46 ), and atherosclerosis ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Purinergic signaling is highly described in tumoral context ( 162 ) and in autoimmune diseases ( 163 ) but poorly studied in the context of cardiac pathologies. Given the high production rate of ATP and the turnover required to maintain its continuous mechanical work, disruption of heart tissue generates the release of high amounts of ATP to the extracellular space.…”
Section: Signaling Pathways and Molecules Modulating Cardiovascular Imentioning
confidence: 99%